The development and piloting of 'Trinity Student Profile' : self report measure for students experiencing mental health problems - Nolan, Clodagh (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Occupational Therapy, 2011)
The Discipline of Occupational Therapy in collaboration with the Disability Service in Trinity College established a support service entitled UNILINK in 2003. This service was developed in direct response to an increasing student population who were experiencing mental health problems from 11 in 2001 to 30 in 2003 (Disability Annual Report 2006). As part of the client centred service development a new instrument was designed to capture and profile the difficulties students with mental health problems were experiencing so that their needs could be met. This instrument was called - The Trinity Student Profile (TSP).
Keywords: Occupational Therapy, Ph.D.; Ph.D. Trinity College Dublin